Factors associated with mothers not practicing breast milk expression initiation and exclusive use of mother’s breast milk after delivery of premature infants in Kelantan - Nor, Wan Haiera Wan (2024)
Initiation of breastfeeding in preterm infants is often more challenging compared with full-term infants due to their physiological immaturity. Preterm newborns have reduced levels of alertness, diminished stamina, and encounter heightened challenges in terms of latching, sustaining sucking, and swallowing as compared to their full-term counterparts. Thus, stage II lactogenesis (milk production) should begin with milk expression, considering the infants’ inability to breastfeed directly due to their immaturity and medical state. This study aimed to determine the factors associated with mothers not practicing breast milk expression initiation within six hours post-delivery and not giving exclusive use of mother's breast milk within 24 hours prior to hospital discharge and six months after the birth of premature infants in Kelantan. A total of 234 women who delivered premature infants at two tertiary hospitals in Kelantan participated in this prospective cohort study. A set of structured questionnaires was used to obtain variables of interest within day 3 to day 7 of infants' admission to the Neonatal Intensive Care Unit (NICU). Follow-up phone calls or WhatsApp were made at discharge and six months after birth to determine the infant feeding practice. Most (87.6%) of the mothers did not initiate breast milk expression after six hours following birth. It was significantly associated with mothers who were not implementing skin to skin contact (SSC) or kangaroo mother care (KMC) Adjusted Odds Ratio (AOR) 2.58, 95% CI: 1.12, 5.95), incorrectly answered EBM may be warmed on fire (AOR 0.40, 95% CI: 0.16, 0.97), and mother did not knew that breast milk expression may be done every 3 hours if premature baby away from the mothers (AOR 15.15, 95% CI: 1.97, 116.76). The proportion of mothers not practicing exclusive use of mother's breast milk within 24 hours prior to hospital discharge was 43.7%. Factors found to be associated with mothers not practicing exclusive use of mother's breast milk within 24 hours prior to hospital discharge were knowledge that mothers who are not with their infants should start breast milk expression within the first six hours after birth (AOR 0.45, 95% CI: 0.22, 0.91), mothers have a problem to express breast milk because she was not prepared for premature delivery (AOR 3.31, 95% CI: 1.10, 9.98), and mother did not have enough time to perform breast milk expression (AOR 0.13, 95% CI: 0.01, 1.33). The proportion of mothers not practicing exclusive use of the mother's breast at six months after the birth of premature infants was 59.1%. It was significantly associated with intention duration to breastfeed the infant for the first six months (AOR 4.00, 95% CI: 0.77, 20.65), barrier of the tired body condition disturbed the mothers to express breast milk (AOR 0.17, 95% CI: 0.05, 0.58) and inadequate milk supply interrupted the mothers to express breast milk (AOR 5.64, 95% CI: 1.41, 22.50). The proportion of mothers who initiated breast milk expression within six hours after delivery and practicing exclusive use of mother’s breast milk at discharge, and six months after delivery of premature infants was still unsatisfactory. Hence, it is imperative that health professionals engage in ongoing education beginning during the prenatal phase to enhance the initiation of breast milk expression and maintain the exclusive breastfeeding practice for six months after delivery of premature infants by using learning modules.